Ransomware and the GDPR. Issue 3 (March 2017) - Green, Andy
Abstract : Ransomware is a unique form of hacking that leaves data intact but still disrupts enterprises around the globe. This special malware encrypts computer files, network file shares and even databases, thereby preventing user access. To release the files, the victim is asked to pay a ransom to the cyberthieves. It is completely diabolical and you would think with such brazen criminal activity, there would be relevant data security laws that would kick in. And there are.